Filling the void: The Asia-Pacific problem of order and emerging Indo-Pacific regional multilateralism. Issue 2 (3rd April 2022) - Wirth, Christian; Jenne, Nicole
ABSTRACT: Thirty years after the downfall of the Soviet-led communist bloc, the United States-led liberal international order is seen as coming to an end. Policymakers have converged on the need to safeguard the "rules-based order" across the newly coined "Indo-Pacific" region. However, policy and scholarly debates lack clarity about what exactly is to be preserved, and why the terms of the "rules-based order" and the "Indo-Pacific" have rapidly found their way into policy debates despite their contested meaning. Analyzing developments in regional multilateralism, we find that mainstream discourses purport static conceptions of order, which are often conflated with United States-centered trans-Pacific alliance relationships. The ensuing problem of order stems in large part from the fact that multilateral projects for building alternate orders, undertaken since the early 1990s, have remained far below their potential. We conclude that emerging forms of multilateral cooperation across the enlarged "Indo-Pacific" region have partially filled this void.